2012
DOI: 10.1177/0333102412441720
|View full text |Cite
|
Sign up to set email alerts
|

Headache attributed to airplane travel (‘airplane headache’): Clinical profile based on a large case series

Abstract: This is by far the largest AH case series ever reported in the literature. The diagnostic criteria that we previously proposed proved to be valid when applied to a large number of patients suffering from this condition. We support its recognition as a new form of headache, to be included in the forthcoming update of the International Headache Society Classification, within '10. Headache attributed to disorder of homoeostasis'. Its formal validation would favour further studies aimed at improving the understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
93
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(106 citation statements)
references
References 23 publications
11
93
2
Order By: Relevance
“…It has been considered that barotrauma associated with trigeminal nerve endings in the ethmoid sinuses causes the frontoorbital pain in this clinical entity. [14][15][16] It has been speculated that the vasodilation in the cerebral arteries which developed during an AHAattack may be induced by prostaglandin E2. 14,17 Although there is no specific treatment or prophylaxis for AHA, it has been demonstrated that several medications including analgesics, nonsteroidal antiinflammatory drugs or triptans may have beneficial effects as prophylactic therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been considered that barotrauma associated with trigeminal nerve endings in the ethmoid sinuses causes the frontoorbital pain in this clinical entity. [14][15][16] It has been speculated that the vasodilation in the cerebral arteries which developed during an AHAattack may be induced by prostaglandin E2. 14,17 Although there is no specific treatment or prophylaxis for AHA, it has been demonstrated that several medications including analgesics, nonsteroidal antiinflammatory drugs or triptans may have beneficial effects as prophylactic therapy.…”
mentioning
confidence: 99%
“…Some maneuvers including compression on pain region, Valsalva maneuver, extension of the earlobe, chewing, or yawning can provide a relief of %25 in pain intensity. [14][15][16][17] Dry-eye is the most common problem in the air travelers. As air humidity in the cabin of the aircraft is often lower than 20% of humidity rate and the air in the pressurized cabin is dehydrated, dryness in both skin and ocular surfaces usually occur.…”
mentioning
confidence: 99%
“…It is a well-established fact that during flight travel various things can happen that shall predispose and make a passenger’s head scuffled. Also, recently several cases of airplane headaches have been published 2-4. In 2007, Mainardi F et al,2 in an interesting case report of a patient who presented with severe bursting headache associated to airplane travel, formalized a list of provisional diagnostic criterion for the symptoms entity and proposed for the inclusions of this type of headache in International classification headache disorders.…”
mentioning
confidence: 99%
“…Also, recently several cases of airplane headaches have been published 2-4. In 2007, Mainardi F et al,2 in an interesting case report of a patient who presented with severe bursting headache associated to airplane travel, formalized a list of provisional diagnostic criterion for the symptoms entity and proposed for the inclusions of this type of headache in International classification headache disorders. Later on in 2012 Mainardi F et al,5 in an online publication carried out a survey of 75 patients suffering from airplane headache with a questionnaire based on previously proposed diagnostic criterion and was proved to be valid when applied to large number of patients suffering from this condition.…”
mentioning
confidence: 99%
“…The authors are to be complimented on a most interesting article (1). 'Airplane headache' may well turn out to be more common than is generally thought.…”
mentioning
confidence: 99%